Water-Oil Separation using Computational Fluid Dynamics Approach: Case Study in Free Water Knockout - Samuel Pangeran Aletheia (Department of Physics, Sebelas Maret University, 2026)
This study presents a comprehensive simulation of the Free Water Knockout process, a prevalent technique in the petroleum industry for separating water from crude oil. Leveraging Computational Fluid Dynamics, the research employs the Euler–Euler approach integrated with an inhomogeneous population balance model and a realizable k–ε turbulence model to capture the complex multiphase dynamics within the separator. A key contribution of this study lies in its validation against field data from an oil facility in South Sumatera, Indonesia, using an independent sample t-test (p = 0.13), confirming the model's reliability. The simulation achieved a separation efficiency of up to 48.46%, which, while moderate compared to centrifuge-based systems, demonstrates competitive performance for gravity-driven Free Water Knockout units under high-throughput conditions. This work advances Computational Fluid Dynamics based of the Free Water Knockout modelling by incorporating coalescence dynamics and turbulence effects, offering a validated framework for optimizing separator design and operation in industrial settings.